Cyprus : Background Paper. (IMF Staff Country Reports; Country Report ;, 1996)
This paper provides background information to the report for the 1995 Article IV Consultation with Cyprus. It reviews developments in the real, fiscal, monetary, and external sectors during the 1990s. The effects of wage indexation when the economy faces an adverse terms-of-trade shock in the context of the IMF staff's medium-term projections are illustrated. The paper analyzes the fiscal effects of financial liberalization by estimating government revenues from financial repression and seignior age, and summarizes other countries' experiences with financial liberalization and their implications for Cyprus.